(untitled) (Research, Society and Development, 2021)
Objective: to discuss the most relevant and beneficial aspects of hypofractionation in breast and prostate radiotherapy, which correspond to the most frequent types of cancers in women and men, respectively, except for non-melanoma skin cancer. Method: An integrative literature review was carried out on important points of hypofractionation in breast and prostate radiotherapy, where articles were selected using the MEDLINE, PUBMED, LILACS, SciELO and Google Scholar platforms, choosing to compose the sample space of the review only published articles from the year 2011. In the choice of articles, those that contained long-term results with a good number of patients, such as meta-analysis, were analyzed. Results: Knowing that in the radiotherapy with hypofractionation, the number of fractions is reduced, the patient can be favored in several aspects, such as the reduction of the treatment period, less exposure to ionizing radiation, advantage in relation to the side effects and, mainly, in the context of the COVID-19 pandemic, hypofractionation can benefit many patients with less trips to the hospital environment.